Colon Cancer-Associated Fusobacterium nucleatum May Originate From the Oral Cavity and Reach Colon Tumors via the Circulatory System - Abed, Jawad; Maalouf, Naseem; Manson, Abigail L.; Earl, Ashlee M.; Parhi, Lishay; Emgård, Johanna E. M.; Klutstein, Michael; Tayeb, Shay; Almogy, Gideon; Atlan, Karine A.; Chaushu, Stella; Israeli, Eran; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Fusobacterium nucleatum is a common oral bacterium that is enriched in colorectal adenomas and adenocarcinomas (CRC). In humans, high fusobacterial CRC abundance is associated with chemoresistance and poor prognosis. In animal models, fusobacteria accelerate CRC progression. Targeting F. nucleatum may reduce fusobacteria cancer progression and therefore determining the origin of CRC F. nucleatum and the route by which it reaches colon tumors is of biologic and therapeutic importance. Arbitrarily primed PCR performed previously on matched same-patients CRC and saliva F. nucleatum isolates, suggested that CRC F. nucleatum may originate from the oral cavity. However, the origin of CRC fusobacteria as well as the route of their arrival to the tumor have not been well-established. Herein, we performed and analyzed whole genome sequencing of paired, same-patient oral, and CRC F. nucleatum isolates and confirmed that CRC-fusobacteria originate from the oral microbial reservoir. Oral fusobacteria may translocate to CRC by descending via the digestive tract or using the hematogenous route during frequent transient bacteremia caused by chewing, daily hygiene activities, or dental procedures. Using the orthotropic CT26 mouse model we previously showed that IV injected F. nucleatum colonize CRC. Here, we compared CRC colonization by gavage vs. intravenous inoculated F. nucleatum in the MC38 and CT26 mouse orthotropic CRC models. Under the tested conditions, hematogenous fusobacteria were more successful in CRC colonization than gavaged ones. Our results therefore provide evidence that the hematogenous route may be the preferred way by which oral fusobacteria reach colon tumors.